2010
DOI: 10.1137/090774860
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Parallel AMG Methods for Approximate Solutions of Linear Systems in CFD Applications

Abstract: In engineering practice quite simple algebraic multigrid (AMG) methods with inexpensive coarse-grid selection and constant interpolation are frequently found to be the method of choice to solve systems of linear equations where accurate solutions of these systems are not needed.In a case study we analyze the poor parallel performance of such algorithms on common multicore cluster architectures and suggest using a class of algorithms with hybrid coarse-grid selection featuring a superior parallel performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…For calculations with more than four parallel processes, the diagrams in Figure show the computing time of two different ways to distribute the processes to the nodes: if at most four processes run on one node, the computing time decreases with increasing number of parallel processes in a relatively uniform manner (a detailed discussion of the parallel performance of AMG in such a configuration can be found in Emans ); if all available eight cores of the cluster nodes are used, the same calculation takes significantly more time, for example, 242.8 s compared with 152.8 s for problem S3 solved with SA‐V‐CG. This is because of the limited on‐chip memory bandwidth.…”
Section: Resultsmentioning
confidence: 99%
“…For calculations with more than four parallel processes, the diagrams in Figure show the computing time of two different ways to distribute the processes to the nodes: if at most four processes run on one node, the computing time decreases with increasing number of parallel processes in a relatively uniform manner (a detailed discussion of the parallel performance of AMG in such a configuration can be found in Emans ); if all available eight cores of the cluster nodes are used, the same calculation takes significantly more time, for example, 242.8 s compared with 152.8 s for problem S3 solved with SA‐V‐CG. This is because of the limited on‐chip memory bandwidth.…”
Section: Resultsmentioning
confidence: 99%
“…Trottenberg et al [10] describe the principal options: either the distributed coarse-grid system is solved in parallel or, at some stage, the system is combined on one of the processors, eventually additional coarse-grids are constructed and system of the coarsest grid is solved directly by one processor. As far as we know, a systematic examination of the practical consequences of the choice of the coarse-grid treatment strategy has not been published yet; according to our own experience, the latter method, referred to as agglomeration in this paper, is appropriate for scalar systems, see Emans [3]. It could be demonstrated that AMG with agglomeration has good convergence properties and shows good parallel efficiency.…”
Section: Introductionmentioning
confidence: 93%
“…A generalised method to compute the optimal relaxation parameter was devised by Yang [11] for symmetric positive definite systems, but, to our knowledge, it did not attain practical relevance since it is too expensive. In our own practical experience poor quality of the coarse-grid solution by the iterative solver can lead to significant deterioration of the convergence rates compared to the serial calculation with the same multigrid method, see Emans [3], in particular if schemes with rapid coarsening such as Smoothed Aggregation are used. The described scheme where the linear system associated with the coarsest grid is solved in parallel by a block-Jacobi scheme is referred to iterative coarse-grid solver; we will use the short IT for this scheme in this paper.…”
Section: Parallel Coarse-grid Treatmentmentioning
confidence: 99%
See 2 more Smart Citations